Durability of Infliximab Is Associated With Disease Extent in Children With Inflammatory Bowel Disease. Issue 6 (June 2016) - Shapiro, Jason M.; Subedi, Shova; Machan, Jason T.; Cerezo, Carolina S.; Ross, Albert M.; Shalon, Linda B.; Silverstein, Jared A.; Herzlinger, Michael I.; Kasper, Vania; LeLeiko, Neal S.
ABSTRACT: Objectives: The aim of the study was to evaluate infliximab (IFX) dosing and treatment durability relative to luminal disease burden in patients with inflammatory bowel disease. Methods: Records from 98 pediatric patients treated with IFX between 2012 and 2014 were reviewed. Disease extent was classified as "limited, " "moderate, " or "extensive" based on cumulative assessment of mucosal involvement. Patients started taking standard 5 mg/kg dosing were compared with those initiated taking 10 mg/kg with regard to treatment durability. Results: Overall, 26.4%, 58.3%, and 70% with limited, moderate, or extensive disease, respectively, started taking a standard IFX dose of 5 mg/kg required therapy escalation. Patients with moderate and extensive disease, started taking the 5 mg/kg per dose, showed statistically significant shorter times to escalation than those with limited disease. The percentage of patients remaining on their initial 5 mg/kg per dose at 12 months was 80.1%, 56.9%, and 40.0% for limited, moderate, and extensive disease, respectively. Among patients started taking 10 mg/kg, 100% remained on this dose. All the patients with limited disease who required dose escalation continued on the higher dose at the time of analysis; however, among those with the most extensive disease, 43% failed escalation because of nonresponse or infusion reaction. Conclusions: Patients with extensive disease started taking 5 mg/kg of IFX were more likely to require dose escalation compared to those with limited or moderate disease. All of the patients with moderate and extensive disease started taking 10 mg/kg of IFX remained on this dose. These results suggest that patients with more extensive disease may benefit from higher initial IFX dosing as it relates to durability of the treatment.